PENGARUH LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Prayogo, Enny; Wijaya, I Nyoman Agus; Handayani, Rini; Maretia, Stella (2021)
This research aims to analyze the influence of liquidity, solvency, profitability and firm size on dividend policies. In addition, this research will also analyze at the same time whether liquidity, solvency and profitability are able to influence dividend policies with firm size variable become variable moderation. The population of this research consists of 100 companies which are registered in index Kompas 100 at the period 2019. The sample from this research consists of 50 companies which is the sampling techniques is census techniques by forming sample frameworks. Hypothetical testing techniques in this research use multiple regression analysis with F and T tests as well as moderation regression analysis are processed using SPSS20. The results of this research show simultaneously liquidity, solvency, profitability and firm size have no effect on dividend policy whereas partially, only variable solvency affects dividend policy. And the results of moderation regression analysis show only profitability variable is capable to influencing dividend policies with firm size become variable moderation.